Benign Paroxysmal Positional Vertigo: Present Perspective - Bhattarai, H (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: BPPV, Benign Paroxysmal Positional Vertigo; Dix-Hallpike procedure; Epley maneuver DOI: 10.3126/njenthns.v1i2.4764 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.28-32